Eggs and hatchlings of the Mexican salamander Pseudoeurycea cephalica (Caudata: Plethodontidae) - Bille, Thomas (1998)
Eggs and hatch1ings of Pseudoeurycea c. cephalica from Parque Nacional Lagunas de Zempoala, Morelos, Mexico are described for the first time. The eggs are similar to eggs of P. cephalica manni and P. belli in being unstranded. Egg capsules resemble P. nigromaculata and P. juarezi in having two gelatinous envelopes. The embryos have extensively webbed hands and feet with a continuous reduction in webbing during embryogenesis, supporting the hypothesis that webbing of the feet is a paedomorphic character. The hatchlings are uniform grayish-black dorsally and slightly paler yentrally. They are robust with broad heads and short tails and lack both yomerine and maxillary teeth. Lack of dentition has previously been found in juveniles of P. belli.